Pengelompokan Kinerja Guru Menggunakan Algoritma K-Means Clustering - Muhammad Al-Hafiz (Graha Mitra Edukasi, 2024)
As information technology develops rapidly in all areas of life, it encourages us to be more creative and innovative in solving existing problems. With today's various technologies, it becomes easier for us to find the right solution to a problem. One of them is the grouping of teacher performance at MTS Ikhwawanuts Tsalits Talun Kenas which is still classified as manual so that the results are not optimal. To overcome this problem, data mining with the K-Means Clustering algorithm method is needed in grouping teacher performance. With the K-Means Algorithm, it is hoped that it will be able to determine the ability of the teacher's performance in the teaching process. As well as helping the principal to make it easier to monitor the performance of teachers who are teaching.